Factors Influencing Recreational Activity Participation Among Academic and Administrative Staff of Federal College of Education, Eha-Amufu, Enugu State, Nigeria - Eze, Thaddeus Nnameka; Dike, Dennis Ogbonna (International Journal of Human Kinetics, Health and Education, 2023)
Participation in recreational activity among Nigerian staff is decreasing; especially in tertiary institutions. Most employees of tertiary institutions in Nigeria exhibit non-chalant attitudes towards active participation in recreational activity despite several benefits of recreation identified by experts. The purpose of the study was to determine the factors influencing recreational activity participation among academic and administrative staff of Federal College of Education, Eha-Amufu (FCEE), Enugu state, Nigeria. Two research questions and one null hypothesis guided the study. The population for the study consisted of all the 356 academic and administrative staff of FCEE. There was no sampling due to a manageable total population. The instrument used for data collection was the factors influencing recreational activity participation questionnaire (FIRAPQ), which was designed by the researcher. The face validity of the instrument was determined through the judgment of five experts from the department of Human Kinetics and Health Education in University of Nigeria, Nsukka. Data analysed from research questions were answered using Spearman‟s rank order correlation (ρ) while the null hypothesis was tested using chi-square statistic. Results among others showed that no relationship existed between psychological factors and recreational activity participation among academic and administrative staff; moderate relationship exists between social factors and recreational activity participation among academic staff and weak positive relationship between social factors and recreational activity participation among administrative staff. There was no significant relationship between recreational activity participation and occupational status. The study recommended among others that a forum such as sensitization and enlightenment programme to enlighten the institutions community on available recreation program to increase their skill level should be mounted.